2022
DOI: 10.3389/fpls.2022.914653
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenous Fertilizer Coated With Zinc Improves the Productivity and Grain Quality of Rice Grown Under Anaerobic Conditions

Abstract: An ample quantity of water and sufficient nutrients are required for economical rice production to meet the challenges of ever-increasing food demand. Currently, slow-release nitrogenous fertilizers for efficient inputs utilization and maximum economic yield of field crops are in the limelight for researchers and farmers. In this study, we evaluated the comparative efficacy of conventional urea and coated urea (zinc and neem) on rice grown under aerobic and anaerobic regimes in greenhouse conditions. For the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…As a critical nutrient, the N plays a key role in Zn sequestrations in the wheat's vegetative and reproductive parts of the wheat 51 , 52 . Nitrogen as a macronutrient enhances vegetative growth by regulating the morphologic, physiological, and biochemical mechanisms 53 . The Zn plays an indispensable role in development by regulating the levels of antioxidants and nucleic acid metabolism, a key part of carbonic anhydrase enzymes involved in auxin biosynthesis 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…As a critical nutrient, the N plays a key role in Zn sequestrations in the wheat's vegetative and reproductive parts of the wheat 51 , 52 . Nitrogen as a macronutrient enhances vegetative growth by regulating the morphologic, physiological, and biochemical mechanisms 53 . The Zn plays an indispensable role in development by regulating the levels of antioxidants and nucleic acid metabolism, a key part of carbonic anhydrase enzymes involved in auxin biosynthesis 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The N release of the SF agrees with the crop nutrient requirement, allowing for the coordination of vegetative and reproductive growth, a reduction in nutrient loss, an improvement in N utilization efficiency and a reduction in topdressing labor costs [ 19 ]. In the past decade, studies on rice [ 20 , 21 , 22 , 23 , 24 ] and wheat [ 25 , 26 , 27 , 28 , 29 ] have reported that the application of SF affects the grain quality by changing the concentrations of protein, starch, oil and mineral elements. However, studies have mainly focused on the grain quality while starch structural and functional properties have received less attention [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%